MODEL SNAIL TRAIL SEBAGAI METODE EVALUASI KINERJA PORTOFOLIO SURAT BERHARGA YANG TEPAT DI MASA KRISIS MONETER - Budi Manggala (Jurnal Manajemen., 2001)
The Indonesian economy is at the edge of a ravine, and is extremely difficult to berestored due the multi dimensional crisis. The frequent bomb explosions, riots andupheavals, make foreign investors reluctant to invest, even those who are already here arenow prepared to leave Indonesia.The Indonesian economic recovery is indeed very slow, even the slowest amongother Asian Countries which in the mid 1997 were also hit by the monetary crisis.The objective of the paper is to describe Snail Trail Model about measurement onfinancial portfolio in the long term and a fit s model when entering the monetary crisis inthe current time.Snail trai/ s Model is a financial portfolio theory among a varity of concepts andmodels such as model of Treynor s index, Sharpes Index, and Jensens Index. SnailTrail s Model seeks to understand relations between rate of return and rate of risk fromone or several marketable securities in the long run period.